Effects of acupuncture and moxibustion on heart rate variability in chronic fatigue syndrome patients: Regulating the autonomic nervous system in a clinical randomized controlled trial - Tong Li; Gerhard Litscher; Yudian Zhou; Yanjuan Song; Qing Shu; Li Chen; Qi Huang; Yayuan Wang; Haoran Tian; Rufeng Teng; Hua Wang; Fengxia Liang (Complementary Therapies in Medicine, 2025)
Background: This study investigates the effects of various acupuncture techniques, specific acupuncture points, and their combinations on symptom improvement in chronic fatigue syndrome (CFS) patients as well as their influence on heart rate variability (HRV) indicators. Methods: We recruited 35 healthy subjects as a healthy control group (Group A) and 175 patients with CFS, who were randomly divided into a fake acupuncture group (Group B), an acupuncture group targeting the Zusanli (ST36) point (Group C), an acupuncture group targeting the Guanyuan (CV4) point (Group D), a dual-acupoint acupuncture group (Group E), and a moxibustion group (Group F), with 35 patients in each group. Group B received fake acupuncture at both the bilateral Zusanli and Guanyuan points simultaneously. Group C received acupuncture at the bilateral Zusanli points along with fake acupuncture at the Guanyuan point. Group D received acupuncture at the Guanyuan point along with fake acupuncture at the bilateral Zusanli points. Group E received acupuncture at both the bilateral Zusanli and Guanyuan points simultaneously, and Group F received moxibustion at both the bilateral Zusanli and Guanyuan points simultaneously. Each group received a total of 10 treatments, administered every other day. Before treatment, the Qi-deficiency Syndrome Score, CFS Score, and SF36 Score were assessed for all subjects. HRV was measured before treatment, after the first treatment, after the fourth treatment, and at the end of treatment. Results: The results showed that both acupuncture and moxibustion can effectively alleviate fatigue symptoms in patients suffering from CFS, with combined acupuncture and moxibustion demonstrating greater effectiveness. Conclusion: Acupuncture excelled in regulating the immediate effects of HRV, while moxibustion excelled in regulating long-term effects. Acupuncture targeting both the Zusanli and Guanyuan points proved more effective than acupuncture targeting a single point, with this difference reflected in the distinct regulatory effects on the sympathetic and parasympathetic nervous systems. The intervention mechanism of Zusanli may involve the parasympathetic nervous system, whereas Guanyuan may operate through the sympathetic nervous system. Trial registration: Approved by the Medical Ethics Committee of Hubei Provincial Hospital of Traditional Chinese Medicine (Approval number: HBZY2016-C24-01), and registered with the North American Clinical Trials Data Center (Clinical Trials.gov) (05/10/2016) (registration number: NCT02924831).